Phone Cameras and the Internet as it affects the Photographic Abilities of Students in South-South Nigeria - Uti, Frank .I (Journal of Education and Practice, 2021)
Illustrations when captured using cameras help its mastery, but photographic skills have been hampered by the discovery of the digitalised camera phone manufactured by Samsung and released in South Korea in June of 2000. Photographic skills have further been slowed down by the coming of the internet. To cover this empirical study, one objective and research question was used. The study therefore examined the effects of phone cameras and the internet on the photographic abilities of students in South-South Nigeria. The target population was students who studied Fine and Applied Arts that specialized in graphics. The population only involved the years three and four students. The methodology was a quantitative survey which applied the interview of students and lecturers. The cluster and purposive sampling method was applied. Data was analyzed using simple percentages. Fifty two students in all were interviewed and presenting four questions while those of lectures was eleven presenting two questions. The action of students in this study was greatly influenced by two theories. The theory of social exchange which is maximized by rewards and minimized by costs and the theory of reinforcement, the stimuli coming from the teachers being quiet on the students direction. The results indicated that the student's photographic knowledge was negatively affected by the use of phone cameras and the use of the internet especially on their phones. This situation was accentuated by their teachers not insisting on how or where to obtain illustrations. The recommendations included their lecturers insisting on the use of professional cameras, the university authorities providing quality professional cameras for study purposes and lecturers must insist that students avoid the use of phone camera for their illustrative assignments because its provides another avenue to download and copy.